THE EFFECT OF TRAINING AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE MEDAN CITY FIRE PREVENTION SERVICE - Donny Marasutan Harahap; Sofiyan Matondang; Erwin Pardede (JURNAL PROINTEGRITA, 2019)
Performance can be influenced by many factors, including management factors, abilities, discipline, training and also work motivation. But the most important factors are the factors of training and work motivation. This study aims to determine the effect of training and work motivation partially and simultaneously on employee performance in the Medan City Fire Prevention Service. The population of this study amounted to 250 employees. To determine the number of samples used Slovin formula, obtained as many as 71 people. Data collecti on techniques in this study were questionnaires and documentation studies. While the data analysis technique used is the classic assumption test, multiple regression, t test, F test and coefficient of determination. The results showed that training and work motivation had a positive and significant effect partially and simultaneously on employee performance in the Medan City Fire Prevention Service. The coefficient of determination (R Square) is 0.724. That is, variations in employee performance can be explained by training and work motivation by 72.40%, while the remaining 27.60% is explained by other factors. It is thus recommended that a trainer instructor who truly masters the training material, and design training materials to suit the needs of all the trainees are recommended. Agencies need to pay attention to their employees by providing financial benefits that are comparable to the work charged to the employees concerned. Training and motivation contributed greatly to the performance of the Medan City Fire Fighting Agency, which amounted to 72.40%, but there were still opportunities to improve performance by providing leadership training and career development.